ANALISIS PENERAPAN INDONESIA CASE BASED GROUPS (INA-CBG’S) DALAM PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RUMAH SAKIT KABUPATEN PELALAWAN - Rizky Amalia (PEKBIS, 2020)
There is discrepancy in hospital tariff methods, namely fee for service and BPJSKesehatan tariff method, namely Indonesia Case Based Groups (INA-CBG's) thathave the potential to be beneficial or detrimental to the hospital. This study aims toinvestigate at the factors that influence the difference in tariff. The research methodused was an analytic observational study with a cross sectional approach. The studywas conducted on inpatients in three hospitals in Pelalawan District in 2017. Thesampling technique was consecutive sampling. The analysis model used is amultiple regression analysis model. The results showed that the ward class had asignificant negative influence with the significance value 0.000. The length of stayhas a significant negative influence with the significance value 0.000. The operativeprocedures has a significant negative influence with the significance value 0.000.The severity has a significant positive influence with the with the significance value0.000. The type of hospital has a significant positive influence with the with thesignificance value 0.000.